Structural transformations and characterisation in nano-engineered alloys - Mukherjee S.; Basu J.; Mandal R.K. (My University, 2025)
Structural transformations in the solid state dictate operating regimes of materials for engineering applications. Advanced structural characterisation facilitated by electron microscopy has resulted in significant progress in our understanding of structural transformations across resolvable length scales. We shall confine this communication to one of the metallic systems. This refers to titanium (Ti) alloys. They exhibit formation of a variety of solid solution phases, intermetallic phases, quasicrystals, incommensurate structures, and metallic glasses under different processing conditions. Additionally, newer phase formation at nanometer length scales has also been observed in Ti alloys. The exploration of properties in presence of structures at nanoscale in these alloys have not been discussed in literature extensively. Such an approach will open an avenue for nano-engineered alloys. An attempt will be made to indicate the direction of investigation in this connection succinctly. Understanding the nature and pathways of solid state structural transformations in Ti alloys seem to be important in view of the wide variety of engineering applications. Nanostructured materials have shown formation of newer phases not included in equilibrium phase diagrams. This review shall dwell on this aspect by drawing parallelism from many other alloy systems at nanoscale. In particular, Au−Cu nanostructures will be discussed as an example. It will be argued that size of the system will have influence on the formation of structures that are normally not observed at microscopic length scales in Ti alloys. In view of the complexities involved in phase transformations in Ti alloys, it is important to evolve or look for a model that will help us understand structural transformations by minimum geometrical distortion from a parent phase. Such an approach will offer one of the ways of comprehending formation of phases at nanoscale. In addition to this, it will also help us to consider group-subgroup relationship. It will be shown that unified structural description towards this will be helpful. A brief summary of higher dimensional structural modelling will be presented here with particular reference to phases formed in Ti alloys. © 2023 Elsevier Ltd